Barriers to access to visceral leishmaniasis diagnosis and care among seasonal mobile workers in Western Tigray, Northern Ethiopia: A qualitative study. - Rebecca Marie Coulborn; Tesfay Gebregzabher Gebrehiwot; Martin Schneider; Sibylle Gerstl; Cherinet Adera; Mercè Herrero; Klaudia Porten; Margriet den Boer; Koert Ritmeijer; Jorge Alvar; Abrahim Hassen; Afework Mulugeta (PLoS Neglected Tropical Diseases, 2018)
BACKGROUND:Ethiopia bears a high burden of visceral leishmaniasis (VL). Early access to VL diagnosis and care improves clinical prognosis and reduces transmission from infected humans; however, significant obstacles exist. The approximate 250,000 seasonal mobile workers (MW) employed annually in northwestern Ethiopia may be particularly disadvantaged and at risk of VL acquisition and death. Our study aimed to assess barriers, and recommend interventions to increase access, to VL diagnosis and care among MWs. METHODOLOGY/PRINCIPAL FINDINGS:In 2017, 50 interviews and 11 focus group discussions were conducted with MWs, mobile residents, VL patients and caretakers, community leaders and healthcare workers in Kafta Humera District, Tigray. Participants reported high vulnerability to VL among MWs and residents engaged in transitory work. Multiple visits to health facilities were consistently needed to access VL diagnosis. Inadequate healthcare worker training, diagnostic test kit unavailability at the primary healthcare level, lack of VL awareness, insufficient finances for care-seeking and prioritization of income-generating activities were significant barriers to diagnosis and care. Social (decision-making and financial) support strongly and positively influenced care-seeking; workers unable to receive salary advances, compensation for partial work, or peer assistance for contract completion were particularly disadvantaged. Participants recommended the government/stakeholders intervene to ensure: MWs access to bed-nets, food, shelter, water, and healthcare at farms or sick leave; decentralization of diagnostic tests to primary healthcare facilities; surplus medications/staff during the peak season; improved referral/feedback/reporting/training within the health system; free comprehensive healthcare for all VL-related services; and community health education. CONCLUSIONS/SIGNIFICANCE:Contrary to what health policy for VL dictates in this endemic setting, study participants reported very poor access to diagnosis and, consequently, significantly delayed access to treatment. Interventions tailored to the socio-economic and health needs of MWs (and other persons suffering from VL) are urgently needed to reduce health disparities and the VL burden.